2010
DOI: 10.1063/1.3483763
|View full text |Cite
|
Sign up to set email alerts
|

Density of trap states measured by photon probe into ZnO based thin-film transistors

Abstract: We report on photo-excited trap-charge-collection spectroscopy, contrived to measure the density of deep-level traps near channel/dielectric interface in a working ZnO based thin-film transistor as a function of photon probe energy. Free charges trapped at a certain energy level are liberated by the correspondingly energetic photons and then electrically collected at the source/drain electrodes. During this photo-electric process, the threshold voltage of TFT shifts and its magnitude provides the density-of-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Since electrons trapped at deeper interface states have to be released by photons with higher energy, the corresponding DV th as a function of illumination wavelength can be used to extract the density profile of interfacial states. 10 Second, although the transfer curves plotted in logarithmic scale are nearly parallel to each other in long illumination wavelength range, the SS of the TFT exhibits apparent increase at shorter wavelength. Figure 3 shows the SS values as a function of illumination wavelength revealing a turning point at $ 625 nm, after which the SS continuously increases.…”
mentioning
confidence: 90%
“…Since electrons trapped at deeper interface states have to be released by photons with higher energy, the corresponding DV th as a function of illumination wavelength can be used to extract the density profile of interfacial states. 10 Second, although the transfer curves plotted in logarithmic scale are nearly parallel to each other in long illumination wavelength range, the SS of the TFT exhibits apparent increase at shorter wavelength. Figure 3 shows the SS values as a function of illumination wavelength revealing a turning point at $ 625 nm, after which the SS continuously increases.…”
mentioning
confidence: 90%
“…I D -V G hysteresis and subthreshold slope analysis on TFTs report N it values from ∼2.7 × 10 11 to 5.38 × 10 12 cm −2 for ZnO/HfO 2 [1], [5] and 2.47 × 10 12 cm −2 for Ta 2 O 5 /ZnO [7]. Photoexcited trap-charge collection spectroscopy on Al 2 O 3 /PVP/ZnO structures has been also studied, where D it peaks at 1.31 and 1.37 eV below the conduction band (E C ) were reported with values of 1 × 10 13 and 5.1 × 10 12 cm −2 · eV −1 , respectively [9]. In this letter, the density and energy distribution of electrically active defect states in ZnO/HfO 2 structures is reported based on the admittance spectroscopy (AS) method.…”
Section: Introductionmentioning
confidence: 96%
“…It is suggested that the generation of hydroxyl groups serving as electron traps at channel/dielectric interface could be the main origin of this V th shift , but the detailed physics that are responsible for this have not yet been clarified. Recently, we developed the novel technique of photo‐excited charge‐collection spectroscopy (PECCS) for probing the interfacial trap states . The density of states (DOS) of the interfacial traps could be directly mapped as a function of the photon energy by tracking the change in photo‐induced V th values.…”
Section: Introductionmentioning
confidence: 99%